Triggering receptor expressed on myeloid cells-1 deletion in mice attenuates high-fat diet-induced obesity - Brustolin, Benjamin; Touly, Nina; Maillefer, Marine; Parisot, Lola; Di Pillo, Elisa; Derive, Marc; Gibot, Sébastien (Frontiers in Endocrinology, 2023)
TREM-1 (Triggering Receptor of Expressed on Myeloid Cells-1) is an immunoreceptor mainly expressed by innate immune cells where it plays a crucial role in the amplification of the inflammatory process mediated by Toll-Like Receptor engagement. The low-grade inflammation state present in obesity is responsible for the development and perpetuation of obesity-associated comorbidities (Type 2 diabetes, cardiovascular diseases…). Using primary human cells we showed here that TREM-1 is expressed and functional in subcutaneous and omental (pre-)adipocytes. In vivo, in a mouse model of high-fat diet-induced obesity, we found that Trem-1 deletion limited inflammation, weight gain and insulin resistance. Our findings suggest that TREM-1 plays a significant role in the development of obesity and insulin resistance, and may thus be a novel therapeutic target in this setting.